HPV vaccinations for men and boys. Issue 4 (27th July 2016) - Baker, Peter
Abstract : The issues surrounding HPV vaccination in men and boys was the subject of a recent parliamentary debate. The rationale for a pilot programme of vaccination of men who have sex with men and the slow progress towards all boys receiving the vaccine were discussed, as Peter Baker reports.